Identifikasi Activity Based Management Untuk Meningkatkan Efisiensi Pada Hotel Viona Gresik - Muhajir , Ali; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2023)
This study aims to analyze the role of Activity Based Management in controlling costs in the room division of the Viola Gresik hotel, and to determine the application of Activity Based Management in the room division of the Viona Gresik Hotel to make it more efficient. The method used is descriptive qualitative using data reduction analysis. The results show that the application of the activity based management method is very feasible to use, because with this method there is cost efficiency at Hotel Viola Gresik in the hotel room division, so that from these results it will provide benefits for hotel management by minimizing activity costs and without reducing services. already received by customers.